Análise dos fatores de competitividade da cadeia produtiva da polpa do açaí do nordeste paraense - Araujo, Dinaldo do Nascimento (Universidade Federal de São Carlos, 2017)
The work is dedicated to the study of the açaí pulp chain in northeastern Pará, which is the main production region of the Brazilian açaí. Despite the growth of açaí fruit collection and processing, there is a set of elements that delay the competitiveness of this chain, and the research problem that the work sought to answer was what are the determining factors and what are the critical factors for the competitiveness of the açaí chain. The main objective is to describe and evaluate the impact of the main determinants of the competitiveness of the production chain of the açaí pulp, with focus on the rural production and the processing links. It is provided a characterization of the chain, an identification and evaluation of the main factors of competitiveness and guidelines for future public policies and private strategies. The theoretical basis considered for the research comprises an approach on competitiveness, agrichain and factors of competitiveness. The method used for the execution of the research was the Rapid Appraisal, where semi-structured questionnaires were elaborated for the agents. The main key agents taken into consideration were: açaí producers (farming and extrativism); middleman; representatives of organizations; directors of processing companies and artisan açaí processors. The competitiveness factors defined for this study were: inputs, technology, market structure, governance structure and coordination of the chain, storage and transport and institutional environment. The results achieved are limited to the sample intentionally considered. For the agents of the production link, the factors that positively impact the chain are the technology, market structure and governance structure and coordination of the chain. In the perception of the agents of the processing link, the factors inputs, technology, market structure, governance structure and coordination, storage and transport and institutional environment are neutral for competitiveness. The main critical factors for the competitiveness of the chain were: labor costs, idle fruit processing, conditions and safety of ports and highways, access to credit and better market rates, legalization of the production’s areas, lack of government actions and chagas disease.
Analysis of competitiveness factors of the production chain of the açaí pulp of the northeast paraense
Keywords: Competitividade; Cadeias agroindustriais; Fatores de competitividade; Competitiveness; Agroindustrial chains; Competitiveness factors; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS::ECONOMIA AGRARIA; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA ECONOMICA